Monetary Valuation of Human Capital: Theoretical Framework and Simulation of Modern HRA Models - Damar Jati; Minadi Wijaya; Gawik Setiawan; Fatima Muhammad Abdulkarim (Universitas Ahmad Dahlan, Yogyakarta, 2026)
This research is motivated by the shift toward knowledge-based economies and the rise of start-ups, where human resources are the primary strategic asset but remain unrecognized in conventional accounting. This limitation may lead to an incomplete representation of corporate value and contribute to valuation discrepancies. This study aims to examine and synthesize various monetary valuation models in Human Resource Accounting (HRA) to address the limitations of conventional accounting in recognizing human capital as a strategic asset. The study adopts a qualitative literature review and conceptual analysis, drawing on foundational theories of human resources, including Resource-Based Theory, and major monetary valuation models such as the Lev and Schwartz compensation model, the Flamholtz model of individual and organizational economic value, and the Jaggi and Lau group valuation approach. Through content and comparative analysis, the study evaluates these models based on their theoretical foundations, valuation assumptions, and practical applicability in converting human productivity into monetary value. The synthesis further demonstrates that while individual-based valuation models provide greater measurement precision, organization-level economic value approaches are more suitable for corporate reporting due to their broader applicability. This study provides a unified analytical framework for comparing major monetary valuation models in Human Resource Accounting. Overall, the study concludes that no single monetary valuation model is universally applicable; rather, model selection should align with the intended valuation objective. These findings support more effective human capital valuation and corporate reporting.